Validity and Reliability in Autonomy Needs Scale for Student - A’zam, Muhammad Nazif; Husna, Aftina Nurul; Qomariyah, Laili (Universitas Muhammadiyah Yogyakarta, 2023)
The need for autonomy is how the individual thinks that his behaviour comes from himself without being influenced by others. The formation of autonomy was influenced by seven aspects, namely freedom, initiative, self-confidence, responsibility, self-assertiveness, decision-making, and self-control. The purpose of this study is to determine the validity and reliability of the scale of autonomy needs that are made. This article also to explain specifically about the need for autonomy because there are not many articles that explain about autonomy needs of student. This research involved 92 students from various cities and universities to become subjects. The questionnaire consists of 60 items designed to assess aspects of freedom, initiative, self-confidence, responsibility, self-assertiveness, decision-making and self-control. This questionnaire has five alternative answers, namely 1 for